Preparation and Characterization of Sawdust (Cellulose) as an Adsorbent for Oil Pollution Remediation - Nwufo, Bethrand Tabugbo; Isaac, Nabut Duwilson; Onche, Emmanuel Usman (International Journal of Natural Sciences Research, 2014)
Oil pollution is peculiar to oil producing nations of the world. Various researches have been carried out to cub its menace. However, most of the materials are non-biodegradable and require expensive treatment to become an adsorbent. In this study, adsorptive capacities of cost effective raw hard and softwood sawdust were investigated and compared. Soft wood sawdust was found to have better adsorptive capacities. The adsorptive capacities are related to the mesh size of the sawdust, the concentration of the oil, the quantity of the sawdust and the time of contact of the oil and the sawdust. Maximum uptake of the oil by both adsorbents occurred at 120 and 150 minutes for all the results. This study recommends that further research be done on the use of modified softwood sawdust so as to increase its potential as a low cost adsorbent in oil remediation.